The impact of the War on the Development of Higher Education in Ukraine: Experience for EU Countries - Martynets, L.; Shyba, A.; Kochetkova, I.; Krupiei, K. S.; Rud, A.; Крупєй, Кристина Сергіївна (My University, 2024)
This study investigated the effects of the Russian-Ukrainian war on the progress of higher education in Ukraine and its potential experience for the European Union. The objective of this research was to comprehend the diverse challenges brought about by military circumstances and to examine the role of digital resources in delivering ongoing education during times of war. 141 teachers and 110 students from different regions were involved in the study. The use of a comprehensive methodology included mixedmethods approach. Surveys and interviews were as well used in the research in order to collect feedback on the experiences and views of the participants. The study unveiled major obstacles including the need to move, destruction of infrastructure, limited availability of resources, and emotional strain experienced by both students and teachers. Digital tools such as video lectures, conferences, e-textbooks, and learning platforms proved the importance of continuing education in the context of war. The conclusions emphasised the importance of addressing the impact of war on higher education and provided practical implications for developing coping strategies. Ukraine's experience is an important source of learning for EU countries. It could help them respond more effectively to similar challenges.
Keywords: Russian-Ukrainian war; higher education; digitalisation; challenges; surveys